Targeted Program in an Academic Rheumatology Practice to Improve Compliance With Opioid Prescribing Guidelines for the Treatment of Chronic Pain. Issue 10 (31st August 2021) - Wang, Eric J.; Helgesen, Rebecca; Johr, Chadwick R.; Lacko, Hannah S.; Ashburn, Michael A.; Merkel, Peter A.
Abstract : Objective: The Centers for Disease Control and Prevention (CDC) and many state governments have issued guidelines for opioid prescribing for the treatment of chronic noncancer‐associated pain. We sought to decrease practice variation and increase compliance with these guidelines in a tertiary academic rheumatology practice by developing an interdisciplinary opioid working group and using electronic health record (EHR)–integrated data feedback. Methods: Division leadership and providers established shared goals at interdisciplinary meetings involving rheumatology, pain medicine, nursing, and pharmacy. Interventions included educational sessions on opioid prescribing guidelines and the sharing of individual de‐identified prescribing patterns. An opioid dashboard page within the EHR allowed every provider to see individualized and division‐wide data that tracked process measures based on CDC and state‐specific guidelines. Baseline data from June to August 2017 were compared with monthly data through December 2018. Results: At baseline, 40% of patients had an active opioid agreement (a Pennsylvania guideline and a New Jersey law), 25% had a urine drug screen result within 12 months of their most recent opioid prescription, and 24% had a concurrent benzodiazepine prescription. After 16 months, these percentages improved to 88%, 66%, and 16%, respectively. The average number of opioid tablets prescribed per month decreased from 59, 733 to 48, 966 (–18%; P = 0.02). Conclusion: Shared goals developed through interdisciplinary input and readily accessible data feedback can markedly increase provider compliance with national and state‐specific guidelines for opioid prescribing for the treatment of chronic noncancer‐associated pain in rheumatology.